1946
DOI: 10.1136/hrt.8.1.6
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of the Wenckebach Type of a-v Block

Abstract: The Wenckebach type of auriculo-ventricular block is characterized by a progressive lengthening of the A-V conduction time, ending in a completely blocked auricular complexthe Wenckebach period. These periodically recurring dropped beats were first recognized clinically by Wenckebach in 1899 from a careful analysis of radial arteriograms; Engelmann (1896) had noted the same phenomenon in the frog's heart a few years earlier. Changing conduction times, due to varying degrees of recovery of the A-V junction, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1960
1960
2002
2002

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Lewis and Master (1925) showed that the conduction time of a single premature stimulus through the AV node decreased as the time interval since the last passage of a previous impulse through the AV node increased. The function describing this relationship, the AV nodal recovery curve, can be used to predict the rhythms that arise during atrial stimulation at a rate faster than the intrinsic rate (Decherd and Ruskin, 1946;Shrier et al, 1987). Further work has developed models of AV nodal function describing the response to both periodic and irregular inputs (Heethaar et al, 1973a,b;Cohen et al, 1983;Talajic et al, 1991;Meijler et al, 1996;Zeng and Glass, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Lewis and Master (1925) showed that the conduction time of a single premature stimulus through the AV node decreased as the time interval since the last passage of a previous impulse through the AV node increased. The function describing this relationship, the AV nodal recovery curve, can be used to predict the rhythms that arise during atrial stimulation at a rate faster than the intrinsic rate (Decherd and Ruskin, 1946;Shrier et al, 1987). Further work has developed models of AV nodal function describing the response to both periodic and irregular inputs (Heethaar et al, 1973a,b;Cohen et al, 1983;Talajic et al, 1991;Meijler et al, 1996;Zeng and Glass, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…These include conduction slowing of single premature atrial impulses,1 variable conduction responses to accelerations in rate,23 and different patterns of conduction block seen during Wenckebach periodicity. [4][5][6][7] Several mathematical models of AV nodal conduction have been described. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] However, no single model has yet satisfactorily explained the wide variety of possible AV nodal behavior.…”
Section: A Unified Model Of Atrioventricular Nodal Conduction Predictmentioning
confidence: 99%
“…[4][5][6][7] Several mathematical models of AV nodal conduction have been described. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] However, no single model has yet satisfactorily explained the wide variety of possible AV nodal behavior. For example, the assumptions used to explain one type of behavior such as Wenckebach-type AV block may not correctly account for normal patterns of anterograde conduction of premature atrial impulses13 or may fail to explain time-dependent changes in the pattern of second-degree AV block6,7,14-20 that are observed with prolonged atrial stimulation in humans.7 Moreover, experimental confirmation of theoretical predictions is often lacking13-15 '19 or based on stimulation sequences that are closely related to the original manner in which the model was constructed.…”
Section: A Unified Model Of Atrioventricular Nodal Conduction Predictmentioning
confidence: 99%
“…While Wenckebach periodicity could develop theoretically in a single-pathway model, it is the specific interaction between the two pathways in the intact heart that produces rich variability of Wenckebach patterns. These findings can help to explain some of the paradigmatic mechanisms underlying the atrioventricular conduction [61,141,142,143].…”
Section: Major Findingsmentioning
confidence: 86%
“…One of the first attempts to model the atrioventicular conduction time was done by Decherd et al [61]. In that work, Decherd attempted to unmask the role of the AV node in the Wenckebach periodicity.…”
Section: Models Of the Av Timementioning
confidence: 99%